Sampling of environmental electromagnetic frequencies demonstrates the evolution of the nervous system toward social cognitive reflexes - Hazani, Joseph A. (Frontiers in Computational Neuroscience, 2023)
The aim with this research is to help inspect the evolution of cell life through applying the electrical engineering sciences to the cellular evolution of human neural networks. Using a mathematically rigorous theory of cellular biological progression, the hypothesis will demonstrate that cell life evolves towards increasing the organism’s sampling rates for energy transfer or “exposing points” with its Natural environment. This progress in increasing the sampling points of electromagnetic radiation frequencies available for transfer into its biological system stabilizes cellular reproduction growth cycles as a function of physical motion transfer measurable in volts-ampere or calories/sec.